M-Smart - An Improved Multi-style Engineering Design CAD System for Clothing Thermal Functions (Journal of Fiber Bioengineering and Informatics, 2018)
A virtual CAD system for thermal functional design is reported in this paper. An improved multi-stylegarment design and segmental condition specification was achieved in this system. Moreover, this systempredicted the thermal status of human and clothing system while the predicted results correspond wellwith the experimental results. Both 3D static and dynamic visualization were presented to the users toget a feedback for the design case.
Keywords: Thermal Functional Engineering Database; Multi-style Garment Design; Cad System; Segmental Specify